The Effect of Inflation, Interest Rates, and Exchange Rates on Stock Returns With The Composite Stock Price Index (IHSG) as an Intervening Variable in Indonesia 2016–2025 - Anwar Ramli; Indah Lestari Anwar (Economics and Business Journal (ECBIS), 2026)
This study examines the effect of inflation, interest rates (BI7DRR), and exchange rates (USD/IDR) on stock returns of PT Telkom Indonesia (Persero) Tbk., with the Jakarta Composite Index (IHSG) as an intervening variable. Using a quantitative explanatory research design, monthly secondary data spanning January 2016 to December 2025 (120 observations) were analysed using Pearson correlation and two-stage path analysis (OLS regression). Results indicate that inflation and exchange rates significantly influence IHSG, while the BI Rate does not. However, neither macroeconomic variables nor IHSG significantly affect Telkom's stock returns either directly or indirectly. The model explains only 2.7% of the variation in stock returns, suggesting that company-specific and sectoral factors dominate return determination. These findings imply that IHSG does not serve as an effective mediating channel between macroeconomic conditions and individual stock returns for Telkom. Investors in the telecommunications sector should prioritise fundamental and sectoral analysis over macroeconomic indicators when making portfolio decisions